N6-Methyladenosine RNA Modification: A Potential Regulator of Stem Cell Proliferation and Differentiation - Wei, Bo; Zeng, Meiyu; Yang, Jing; Li, Shuainan; Zhang, Jiantao; Ding, Nan; Jiang, Zhisheng (Frontiers in Cell and Developmental Biology, 2022)
Stem cell transplantation (SCT) holds great promise for overcoming diseases by regenerating damaged cells, tissues and organs. The potential for self-renewal and differentiation is the key to SCT. RNA methylation, a dynamic and reversible epigenetic modification, is able to regulate the ability of stem cells to differentiate and regenerate. N6-methyladenosine (m6A) is the richest form of RNA methylation in eukaryotes and is installed by three subunits: methyltransferase complexes, demethylase complexes and m6A binding proteins. Through the coordination of these proteins, RNA methylation precisely modulates the expression of important target genes by affecting mRNA translation, selective splicing and microRNA maturation. In this review, we summarize the most recent findings on the regulation of m6A modification in embryonic and adult stem cells, hoping to provide new insights into improving SCT technology.